2022
DOI: 10.3390/ani12223112
|View full text |Cite
|
Sign up to set email alerts
|

Suckling Induces Differential Gut Enzyme Activity and Body Composition Compared to Feeding Milk Replacer in Piglets

Abstract: The aim of this study was to investigate differences in growth, hematology, metabolism, small intestine (SI) morphology, and enzyme activity of sow-reared piglets (SOW) compared to artificially reared piglets (MILK) given milk replacers in two different environments. Thirty-six piglets were selected at birth based on their birth weight; eighteen were kept on a commercial farm, another eighteen transferred to an animal research facility for artificial rearing. Differences were observed in enzymatic activity, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(34 reference statements)
1
1
0
Order By: Relevance
“…[48]formula due to the risk of diarrhea, based on earlier experience from other studies at our research facilities. Therefore, a lower growth rate in our piglets was expected compared to sow-reared piglets under conventional settings, which corresponds with the ndings in Amdi et al, [49]. However, no differences in growth was observed between the three intervention groups and CON.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…[48]formula due to the risk of diarrhea, based on earlier experience from other studies at our research facilities. Therefore, a lower growth rate in our piglets was expected compared to sow-reared piglets under conventional settings, which corresponds with the ndings in Amdi et al, [49]. However, no differences in growth was observed between the three intervention groups and CON.…”
Section: Discussionsupporting
confidence: 86%
“…Due to the absence of the most common pathogens in the donor material and the occurrence of diarrhea in both the CON group and the experimental group, it is more likely that the diarrhea episodes were a result of the stress of single housing and shift from sows milk to milk replacer. Previous studies have demonstrated that such a transition can impact the integrity of the small intestinal barrier and raise the likelihood of experiencing diarrhea (49). Notably, the overall high prevalence of spontaneous diarrhea among all groups may have masked the treatment effects and should therefore be regarded as a limitation of the study.…”
Section: Discussionmentioning
confidence: 98%